Barriers in health and social care access and navigation for elder orphans: a scoping review protocol. Issue 5 (31st May 2021) - Kervin, Lucy; Teo, Kelly; Churchill, Ryan; Riadi, Indira; Cosco, Theodore D
Abstract : Introduction: Family members have traditionally been relied on to provide informal care to older adults. However, social and demographic changes are resulting in rising numbers of kinless and isolated elderly who are unable to rely on familial caregiving and are without assistance in navigating complex systems of health and social services. Research examining this vulnerable subset of the elderly population, identified as elder orphans, is limited, particularly within the context of health and social care access. The aim of this scoping review is to map and report the evidence available in identifying barriers and facilitating factors in health and social care access and system navigation by elder orphans. Methods and analysis: Arksey and O'Malley's six-staged methodology framework will guide the conduct of this scoping review. The primary author will conduct a systematic search and an initial screen of titles and abstracts from six electronic databases (CINAHL Complete, ASSIA, Pubmed, Scopus, Web of Science and PsycINFO) from January 2005 to the date of commencement, to identify English language peer reviewed studies of various methodologies. Subsequently, two reviewers will independently screen a shorter list of studies for inclusion. We will also search the reference lists of eligible studies. Data from the selected studies will be extracted and charted by two independent reviewers. Findings will be summarised in a tabulated format and accompanied by a narrative synthesis. Ethics and dissemination: As the scoping review methodology aims to synthesise information from publicly available materials, this study does not require ethical approval. The finalised scoping review will be submitted for publication to a scientific journal. Registration: The present protocol has been registered with the Open Science Framework platform (registration ID: https://osf.io/7vjty/ ).